2016
DOI: 10.1109/ted.2016.2516921
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fin-Edge Roughness and Metal Grain Work Function Variability in InGaAs and Si FinFETs

Abstract: Copies of full items can be used for personal research or study, educational, or not-for profit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way.Publisher's statement: "© 2016 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…3 (bottom). As previously reported for LER [26], GER variability will increase with the RMS. We obtain maximum variability values at a RMS value of 1.0 nm, where σV T and σlog 10 (I OFF ) are 34% and 18% larger for the FinFET than for the GAA NW FET, respectively.…”
Section: Ger Variabilitysupporting
confidence: 79%
“…3 (bottom). As previously reported for LER [26], GER variability will increase with the RMS. We obtain maximum variability values at a RMS value of 1.0 nm, where σV T and σlog 10 (I OFF ) are 34% and 18% larger for the FinFET than for the GAA NW FET, respectively.…”
Section: Ger Variabilitysupporting
confidence: 79%
“…12 shows the OFF-current (I OFF,high ) versus the threshold voltages ( The 22 nm gate length GAA NW shows smaller variations for the four figures of merit at low and high drain biases than the ones observed in the 10 nm gate length GAA NW (see Fig. 8) as expected but the increase in the device variability is relatively small when comparing correlation coefficients (CC) [6], [7]. This demonstrates that the GAA NW FETs are strong candidates for future generation of digital transistors delivering large on-current required in a circuit design accompanied by a well controlled device variability.…”
Section: Nm) the Threshold Voltage At Low And High Drain Biasesmentioning
confidence: 56%
“…With respect to the MGG, we have limited the study to devices with an average grain size (GS) of 7 nm. An in-depth study of the influence of the grain size can be found in [27]. An example of a metal gate profile from the grain size of 7 nm is shown in Fig.…”
Section: A Metal Grain Granularitymentioning
confidence: 99%
“…When studying the influence of the LER, we have limited the analysis to devices with a correlation length (CL) of 10 nm and a root mean square (RMS) height of 0.8 nm, considering uncorrelated fin edge roughness variations. These values were chosen to represent the ones observed in experimental devices [27]. Fig.…”
Section: B Line Edge Roughnessmentioning
confidence: 99%